Sizing Up Objects: The Effect of Diminutive Forms on Positive Mood, Value, and Size Judgments - Parzuchowski, Michał; Bocian, Konrad; Gygax, Pascal (Frontiers in Psychology, 2016)
Language (e.g., structure, morphology, wording) can direct our attention towards the specific properties of an object, in turn influencing the mental representation of that same object. In this paper, we examined this idea by focusing on a particular linguistic form of diminution used in many languages (e.g., in Polish, Spanish, Portuguese) to refer to an object as being “smaller”. Interestingly, although objects are usually considered “better” when they are bigger in size, objects described with linguistic diminution can also refer to those that are emotionally positive. Across three experiments conducted in Polish, we examined this lexical ambiguity in terms of mood (Experiment1), subjective quality and monetary value (Experiment 2), and choice selection (Experiment 3). Overall, we found that people evaluate objects differently depending on the linguistic form (i.e., with or without diminution) with which they are described, and that it was related to the perceptual representation of these objects, and not their affective status. Objects described with diminution are evaluated as less satisfying and of lesser value and this effect is attributed to the way participants represent the objects (i.e., encoded and memorized). The generalizability of these effects is discussed.